Reliable quantification of mercury in natural waters using surface modified magnetite nanoparticles. (April 2019) - Tavares, Daniela S.; Vale, Carlos; Lopes, Cláudia B.; Trindade, Tito; Pereira, Eduarda
Abstract: Reliable determination of mercury (Hg) in natural waters is a major analytical challenge due to its low concentration and to the risk of Hg losses or contamination during sampling, storage and pre-treatment of samples. The present work proposes a simple, efficient, sensitive and easy-handling methodology for extraction, pre-concentration and quantification of total dissolved mercury in natural waters, using iron oxide nanoparticles (NPs) coated with silica shells functionalized with dithiocarbamate groups (Fe3 O4 @SiO2 SiDTC). Ten mg L −1 of these NPs were sufficient to remove 83–97% of 500 to 10 ng L −1 of Hg in ultra-pure water and artificial seawater, used as model Hg solutions, within 24 h. Mercury sorbed to the NPs was then measured directly by thermal decomposition atomic absorption spectrometry with gold amalgamation. The detection limit of approximately 1.8 ng L −1 is lower than the values reported in dispersive solid phase extraction for other magnetic sorbents. As a proof-of-concept, the proposed methodology was successfully tested in real samples of fresh and saline waters and more than 91% of Hg was recovered. With this methodology the extraction and pre-concentration steps may be carried out in situ decreasing the risk of Hg losses or contamination during sampling, storage and pre-treatment of water samples. Graphical abstract: Image 10 Highlights: Simple methodology for quantify mercury at concentrations currently found in waters. Direct analysis of Hg on the Fe3 O4 @SiO2 SiDTC nanoparticles using a mercury analyser. 10 mg L −1 of nanoparticles can extract more than 90% of the total Hg in waters. The LOD achieved is lower than values reported for other magnetic materials.